Prospects for Regional Development of Industrial Tourism in View of the Analysis of the Main Economic Indicators of Russian Tourism Industry - Yashalova Natal'ya N.; Akimova Mariya A.; Ruban Dmitrii A.; Boiko Stanislav V.; Usova Anna V.; Mustafaeva Ellada R. (Economic and Social Changes: Facts, Trends, Forecast, 2017)
The development of tourism industry at the regional level is relevant for all the subjects of the Russian Federation. The issue is especially acute in those of them that do not have rich cultural-historical heritage and unique natural-climatic conditions. In particular, these areas include highly urbanized industrial regions of the country, which at present do not make an effective use of their potential for the development of domestic and inbound tourism. The subject of the research in this paper is tourist activity in federal districts of the Russian Federation. The purpose of the paper is to analyze the volume of tourist services in the Russian Federation and to substantiate the development of industrial tourism in the regions for the purpose of attracting additional tourist flows. The study uses the system approach, the basic scientific methods of analysis and synthesis, deduction and induction, and statistical analysis methods. One of the innovations in the tourism business of the Russian Federation could be the organization and conducting of excursions to the enterprises of the country not only for official delegations and business partners, but also for ordinary tourists. The article highlights the opportunities and threats for the development of industrial tourism in the Russian Federation. As a result of the statistical analysis of economic indicators of tourism industry development for 2011–2015, the authors identify a decline in the growth rate of the volume of tourist services. The lack of new tourist offerings reduces opportunities for growth. In this case the authors find it appropriate to promote a new type of domestic tourism associated with visiting industrial enterprises. The development of industrial tourism provides the regional economy with the multiplier effect including the stimulating effect on the activity of related sectors, and promotes import substitution in tourism. Main provisions of the present paper, due to their their universal character, can be used in educational process by educational institutions; they can also be recommended for use by the authorities in order to promote regional tourism